Partitioning of fibrinolytic protease from Bacillus sp. UFPEDA 485 by aqueous two-phase systems using PEG/sodium sulfate - Souza, F.A.S.D. (2012)
XI Reunião Regional Nordeste da SBBq | 4th International Symposium in Biochemistry of Macromolecules and Biotechnology